Autobiography of Thomas Jefferson Thomas Jefferson - Jefferson, Thomas (Blacksburg A & D, 2009)
Thomas Jefferson was the third President of the United States and the principal author of the Declaration of Independence. Jefferson was one of the most influential Founding Fathers for his promotion of the ideals of republicanism in the United States. As a political philosopher, Jefferson was a man of the Enlightenment and knew many intellectual leaders in Britain and France. He idealized the independent yeoman farmer as exemplar of republican virtues, distrusted cities and financiers, and favored states' rights and a strictly limited federal government. Jefferson supported the separation of church and state and was the author of the Virginia Statute for Religious Freedom. Here is his life in his own words.
Keywords: Thomas Jefferson; President; U.S.A